JAULUNG WISMAR SARAGIH DAN IDENTITAS GEREJA ETNIK KOMUNITAS KRISTEN SIMALUNGUN SUMATRA TIMUR DALAM ERA POSKOLONIAL - Hartutik (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2022)
The problem in this literature research is the emergence a figure of Jaulung Wismar Saragih (JWS) as a pioneer of the establishment at Simalungun ethnic church in East Sumatra. The purpose of this literature research is to find out the biography of JWS, the arrival of Christians in Simalungun during the Colonial period, and JWS's efforts in establishing the ethnic church of the Simalungun Christian community. This study is a library research with historical research methods through the stages of heuristics, criticism, interpretation, and historiography. The results showed that JWS was one of the driving figures in making changes to the order of Christian life in Simalungun. During the colonial period, the role of JWS as an opponent of the policies of the RMG zendeling occurred in several lines of life. Problems arise when the Simalungun people feel discriminated against by the colonial government in which migrants are prioritized in the involvement of government administration. Problems continued in the realm of Christianity between immigrants and local residents so that a hegemony of resistance emerged, then gradually in the postcolonial era a local ethnic church was established as a symbol of strengthening the identity of the locality. So that we can clearly see that in his life JWS accepted a new element of Christianity through zending and also the idea of ​​Social Progress, as well as emancipation through zending along with Western-Colonial culture that stopped in the Simalungun area. In that case there are conflictual processes, resistance and adaptation to foreign elements that arise. The implication of this research is the importance of a religious identity of an ethnicity so that it can become a symbolically unifying spirit. The limitations of this study are only about Simalungun and the ethnic church at the postcolonial era and not to the discussion of the development of current conditions.